Role of Tomato (Solanum lycopersicum) in Management and Prevention of Four Most Common Cancer in Indonesia - Zulfa, Lathifah Dzakiyyah; Salim, Dessyani; Silalahi, Abigail Tirza (Talenta Publisher, 2022)
Introduction: The rate of new cancer cases in Indonesia is very high. With various risk factors, cancer becomes easier to attack individuals, but that does not mean these factors cannot be changed. One of the modifiable risk factors of cancer is diet from food. Objective: This review aims to investigate the role of chemical compound in tomato (S. lycopersicum) in management and prevention of breast, cervix uteri, lung, and liver cancer. Method: Method for writing this review is by searching for literature published in 2012 - 2020 was carried out to prove the effect of tomatoes on cancer incidence through in vitro, in vivo, and clinical studies. Results: Lycopene in tomatoes has been shown to withstand the cell cycle, inhibit NF-кB, and affect enzymes that produce toxic metabolites, thus preventing the development of various types of cancer. Other active compound such as carotenoid lutein can act as cytotoxic agents by increasing p53 phosphorylation and suppressing the expression of anti-apoptotic genes in breast cancer cells. Interaction between tomatine or tomatidine (another compound in tomatoes) with EGFR will prevent the development or metastasis of non-small cell lung carcinoma. Conclusion: These facts can be concluded that tomato (with various active compound in it) consumption potentially strong in preventing breast, cervix uteri, lung, and liver cancer. Further research should clarify the recommended tomato active compound level for daily consumption and its long-term side effect. Keywords: cancer, diet, Solanum lycopersicum Pendahuluan: Tingkat kasus baru kanker di Indonesia sangatlah tinggi. Terdapat 65.858 kasus baru kanker payudara pada 2020. Dengan berbagai macam faktor risiko, kanker menjadi lebih mudah menyerang individu, namun bukan berarti faktor tersebut tidak dapat diubah. Salah satu faktor risiko yang dapat dimodifikasi adalah diet. Tujuan: Ulasan ini bertujuan untuk membahas bagaimana konsumsi tomat dapat mengurangi risiko terkena kanker maupun memperbaiki prognosis penderita kanker. Metode: Metode penulisan ulasan ini adalah mencari literatur yang dipublikasi selama 2016 – 2021 secara daring dilakukan untuk membuktikan pengaruh tomat terhadap kejadian kanker baik secara in vivo, in vitro, serta penelitian klinis. Hasil: Lycopene yang terkandung pada tomat terbukti menahan siklus sel, menginhibisi NF- B, dan menekan efek enzim yang memproduksi metabolit beracun sehingga bermanfaat dalam mencegah perkembangan berbagai jenis kanker. Bahan aktif lain seperti karotenoid lutein mampu bertindak sebagai agen sitotoksik yang meningkatkan fosforilasi p53 dan menekan ekspresi gen anti – apoptotic pada sel kanker payudara. Interaksi tomatine dan tomatidine (kandungan lain pada tomat) dengan EGFR akan mencegah perkembangan maupun metastasis non-small cell lung carcinoma. Kesimpulan: Beberapa fakta tersebut dapat disimpulkan bahwa konsumsi tomat berpotensi mencegah kanker payudara, serviks uteri, paru – paru, dan hepar. Penelitian selanjutnya perlu membuktikan berapa rekomendasi banyaknya konsumsi tomat harian. Kata Kunci: diet, kanker, tomat